EFFECT OF MANAGERIAL OWNERSHIP, CEO POWER, AND FINANCIAL PERFORMANCE ON CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE POLICY.: (Case Study of 50 Companies Listed on the Indonesia Stock Exchange 2017-2019) - Fitri Komariyah (Media Mahardhika, 2022)
This study aims to prove the significance of managerial ownership and company financial performance on corporate social responsibility reporting. The method used in this article is quantitative with a regression analysis tool. The results of the research state that managerial ownership does not have a significant effect on corporate social responsibility reporting, while management strength has a significant and negative effect on corporate social responsibility reporting, Leverage has a significant effect on corporate social responsibility reporting, but return on assets has no significant effect on corporate social responsibility reporting. corporate social responsibility reporting.